Influence Of Price Discount, In-Store Display, And Shopping Lifestyle On Impulse Buying At Umama Gallery Sidoarjo - Nur Hidayah, Meizar; Komala Sari, Dewi (Universitas Muhammadiyah Sidoarjo, 2021)
This study aims to determine the effect of price discount, in-store display, and shopping lifestyle on impulse buying at Umama Gallery Sidoarjo. The method used in this research is a quantitative approach. Sampling was done by using non-probability sampling method with purposive sampling type with a total of 100 respondents who had visited and bought products at Umama Gallery Sidoarjo. The data analysis technique in this study uses multiple linear regression using the IBM SPSS Statistics version 21 program. The results show that price discount have an influence on impulse buying, in-store display have an influence on impulse buying, shopping lifestyle has an influence on impulse buying, and price discount, in-store display, and shopping lifestyle have a simultaneous influence on impulse buying.